The SPIFFI image slicer: Revival of image slicing with plane mirrors - Tecza, M; Thatte, N; Eisenhauer, F; Mengel, S; Roehrle, C; Bickert, K (Society of Photo-Optical Instrumentation Engineers, 2000)
SPIFFI (SPectrometer for Infrared Faint Field Imaging) is the integral field spectrograph of the VLT-instrument SINFONI (SINgle Far Object Near-infrared Investigation). SINFONI is the combination of SPIFFI with the ESO adaptive optics system MACAO (Multiple Application Concept for Adaptive Optics) offering for the first time adaptive optics assisted near infrared integral field spectroscopy at an 8m-telescope. SPIFFI works in the wavelength ranger from 1.1 to 2.5 micron with a spectral resolving power ranging from R=2000 to 4500. Pixel scale ranges from 0.25 to 0.025 seconds of arc. The SPIFFI field-of-view consists of 32x32 pixels which are rearranged with an image slicer to a form a long slit. Based on the 3D slicer concept with plane mirrors, an enhanced image slicer was developed. The SPIFFI image slicer consists of two sets of mirrors, called the 'small' and the 'large' slicer. The small slicer cuts a square field of view into 32 slitlets, each of which is 32 pixels long. The large slicer rearranges the 32 slitlets into a 1024 pixels long slit. The modifications to the 3D slicer concept affect the angles of the plane mirrors of small and large slicer and lead to an improved slit geometry with very little light losses. At a mirror width of 0.3mm the light loss is <5%. All reflective surfaces are flat and can be manufactured with a high surface quality. This is especially important for the adaptive optics mode of SINFONI. We explain the concept of the SPIFFI mirror slicer and describe details of the manufacturing process.